Iqbal: an intellectual with a vision and mission (Part One) - Abdul Razak, Mohd Abbas (Mission Soft Foundation, 2022)
Iqbal, who was well-known by the title Allama Mohamed Iqbal, was born on 22nd Feb.1873, in Sialkot, a place in northern India. His roots go back to his ancestors, who originated from the region of Kashmir in the Indian subcontinent. Prior to their conversion to Islam, his ancestors belonged to the upper-class Brahmin of the Hindu caste system. They were guided towards the religion of Islam by the preachings of Syah Hamdani, a pious religious personality who lived during the time of the last ruler of the Mogul dynasty. The fall of the Mogul dynasty made Iqbal’s ancestors migrate from Kashmir to Sialkot (Mohd Abbas, 1992).